2020
DOI: 10.1155/2020/8829212
|View full text |Cite
|
Sign up to set email alerts
|

Pantoprazole (PPZ) Inhibits RANKL-Induced Osteoclast Formation and Function In Vitro and Prevents Lipopolysaccharide- (LPS-) Induced Inflammatory Calvarial Bone Loss In Vivo

Abstract: Bone remodeling is a process delicately balanced between osteoclastic bone resorption and osteoblastic bone formation. Osteoclasts (OCs) are multinucleated giant cells formed through the fusion of monocytic precursors of the hematopoietic stem cells lineage. OCs are the exclusive cells responsible for the resorption and degradation of the mineralized bone matrix. Pantoprazole (PPZ), a proton pump inhibitor (PPI), is commonly prescribed to reduce excess gastric acid production for conditions such as gastroesoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Loss of RANKL in mice results in severe osteopetrosis, while overexpression of soluble RANKL leads to severe osteoporosis ( Kong et al, 1999 ; Mizuno et al, 2002 ). When monocytes expressing RANK, a member of the TNF receptor family, are exposed to RANKL, they merge to create multinucleated osteoclasts ( Li Y.-X. et al, 2020 ).…”
Section: The Differentiation Of Osteoclastsmentioning
confidence: 99%
“…Loss of RANKL in mice results in severe osteopetrosis, while overexpression of soluble RANKL leads to severe osteoporosis ( Kong et al, 1999 ; Mizuno et al, 2002 ). When monocytes expressing RANK, a member of the TNF receptor family, are exposed to RANKL, they merge to create multinucleated osteoclasts ( Li Y.-X. et al, 2020 ).…”
Section: The Differentiation Of Osteoclastsmentioning
confidence: 99%
“…18 TAK1/TAB2, which is a downstream protein of TARF6 in the RANK signaling pathway, activates JNK with p38 protein. 27 Furthermore, downstream signaling of the ERK and JNK pathways include AP-1 transcription factors, Fos family dimers (c-Fos, FosB, Fra-1, and Fra-2) and Jun family (c-Jun, JunB, and JunD). 28 ERK could induce and activate c-Fos, while JNK could enhance the transcriptional activity of AP-1 through the phosphorylation of c-Jun.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors are involved in the process of LPS-induced bone loss, including the local host response, production of prostaglandins and cytokines, and recruitment of inflammatory cells [ 10 , 11 ]. Recent studies have indicated that the bone loss caused by LPS is not only due to osteoclast activation, but also the inhibition of osteoblast function [ 12 14 ]. LPS promotes osteoblast apoptosis and inhibits osteoblast differentiation via activation of the JNK pathway in MC3T3-E1 cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%